Post-intervention outcomes in farmer behaviour and crop diversification in Rajshahi, Bangladesh - Nandi, Ravi; Hossain, Md. Khaled; Anupama Islam Nisho; Saiful Islam; Alanuzzaman Kurishi, A.S.M.; Sumona Shahrin; Mustafa Kamrul Hasan; Md. Arifur Rahaman; Krupnik, Timothy J. (TAFSSA, 2024)
This brief summarizes the results from post-intervention outcomes in farmer behavior covering a) preferred cropping patterns among farmers; b) perceived benefits, challenges, and transaction costs of crop diversification, and c) market awareness among trial farmers. Data were collected through face-to-face surveys involving on-farm trail farmers in the Rajshahi district.